Scission of electrospun polymer fibres by ultrasonication - Marini, Sawawi (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The scope of this research is to study the use of uitrasonication, using a probe sonicator to produce short fibre from electrospun webs of four types of polymer poly(styrene) (PS), poly(methyl methacrylate) (PMMA), poly(acrylonitrile)(PAN) and poly(L-lactic) acid (PLLA). Scissioning of the usually long, continuous non-woven electrospun web would be useful as a means to produce short discrete fibres in significant amounts. Such materials are useful for numerous applications, including composite reinforcement and biomedical applications such as vessels for the containment and release of drugs. Optimisation of the electrospinning parameters were carried out to produce electrospun fibres from the four polymers that were beads-free, and whose nanofiber constituents had submicron diameters. It was found by producing and testing non-woven webs that had roughly similar fibre diameters, as well as similar tensile strength and elastic modulus, that the ductility of the electrospun polymer was the key determinant as to whether the web could be ultrasonically scissioned. Thus, ultrasonication is an effective method to scission brittle/submicron electro spun fibre such as PS and PMMA, whilst post-treatments such as UV -Ozone irradiation and heat treatment of the electro spun fibres were required for polymers such as PAN and PLLA. Without such post-treatment, PAN and PLLA were unable to be scissioned, regardless for how long the samples were sonicated. The success of the post-treatments was due to either reductions in ductility reduction or induced flaws on the electrospun fibres, the IV latter acting as points for the initiation of failure, facilitating the scissioning of these more ductile materials.